2013
DOI: 10.1111/j.1742-9544.2011.00046.x
|View full text |Cite
|
Sign up to set email alerts
|

Profiling a Profession: A Victorian Survey Assessing Lay Attitudes Toward and Knowledge of Counselling Psychologists

Abstract: The current study employed a mixed‐methods approach to examine perceptions towards and knowledge of counselling psychologists, including perceived differences between counselling and clinical psychologists. One hundred and fourteen adult members of the Victorian general public participated in the study and completed a 65‐item questionnaire, the Counselling Psychology Status Survey. As predicted, results from quantitative analysis showed that counselling psychologists were reported to be highly needed, valued, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
(75 reference statements)
0
4
0
Order By: Relevance
“…This finding raises important questions about how counselling psychologists may be viewed in the public sphere as compared to clinical psychologists. In a recent survey (7 years after the introduction of Better Access ) exploring Victorian lay attitudes towards and knowledge of counselling psychologists, McKeddie () found a primarily positive public image with some clear limitations. Counselling psychologists were perceived as dealing with less severe problems and relationship difficulties, while clinical psychologists were seen as working with complex and life‐threatening problems.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding raises important questions about how counselling psychologists may be viewed in the public sphere as compared to clinical psychologists. In a recent survey (7 years after the introduction of Better Access ) exploring Victorian lay attitudes towards and knowledge of counselling psychologists, McKeddie () found a primarily positive public image with some clear limitations. Counselling psychologists were perceived as dealing with less severe problems and relationship difficulties, while clinical psychologists were seen as working with complex and life‐threatening problems.…”
Section: Discussionmentioning
confidence: 99%
“…Throughout the 1980s and 1990s, counselling psychology thrived in Australia—there was an expansion in training programs and active research in the field, represented in the Australian Journal of Counselling Psychology . Both clinical and counselling psychology professionals were able to operate alongside each other in health settings (Brown & Corne, ; McKeddie, ; Pelling, ) and it seemed that although there were similarities between clinical and counselling psychologists, there were also significant differences in training and philosophy (McKeddie, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, licensed counselors indicated they perceived themselves as a unique profession with a different focus than psychologists and social workers (Mellin et al, 2011). It is not surprising that there has been consistent role confusion for individuals who seek mental health care since there is disagreement in the professional field itself (McKeddie, 2013;Murstein & Fontaine, 1993;Robiner, 2006). Individuals should be knowledgeable of these differences as "clearer articulation of disciplines' respective scopes of practice and training models potentially could enhance consumers' understanding of their choices" between mental health professionals (Robiner, 2006, p. 614).…”
mentioning
confidence: 99%